PELATIHAN PEMBUATAN PUPUK ORGANIK PADAT (BOKASHI) BAGI PEMUDA KLASIS ALTAR SEBAGAI UPAYA MENDUKUNG PERTANIAN BERKELANJUTAN - Karbeka, Martasiana; Mallau, Salomi; Maata, Julinda; Manimoy, Herianus; Mautuka, Zakarias (MAJU : Indonesian Journal of Community Empowerment, 2025)
This community service activity was carried out by the Chemistry Study Program of Tribuana Kalabahi University (UNTRIB) in collaboration with the Altar Youth Classis, with the aim of increasing the knowledge and skills of young people in utilizing local organic materials to make bokashi-type solid fertilizer. Alor Regency has abundant natural resource potential, but the still traditional agricultural system and dependence on inorganic fertilizers are major challenges. Through this activity, young people were trained to process organic materials such as goat manure, lamtoro leaves, banana stems and other organic materials as well as household waste with the help of effective microorganism fermentation (EM4) into environmentally friendly and economically valuable bokashi fertilizer. This activity included the delivery of materials, a question and answer session about fertilizer making, and direct mentoring by lecturers and students of the UNTRIB Chemistry Study Program. The results of this activity showed an increase in the participants' understanding and skills in the fermentation process, organic waste management, and the application of chemical principles in agricultural practices. Thus, this training is expected to encourage youth independence in the agricultural sector while strengthening collaboration between universities and the community in realizing sustainable agriculture based on local wisdom.